Functional Disability After Ischemic Stroke: A Community-Based Cross-Sectional Study in Shanghai, China - Yao, Ying-Ye; Wei, Zi-Jun; Zhang, Yue-Chan; Li, Xiang; Gong, Liu; Zhou, Jia-Wei; Wang, Yu; Zhang, Yun-Yun; Wang, Rui-Ping (Frontiers in Neurology, 2021)
Objective: This study aimed to understand the demographics, functional disabilities, cognitive impairment, and depressive mood among stroke patients and to explore the correlation between functional disability and the other health conditions so as to provide some data for community rehabilitation among stroke patients. Methods: A cross-sectional study was conducted to investigate the functional status of ischemic stroke patients with stroke history between 1 month and 2 years by applying the modified Rankin Scale (mRS). Data were collected during October 2016 and January 2017 from 11 communities in two districts of Shanghai, China. We used face-to-face questionnaire interviews to collect information on sociodemographics, vascular risks associated with stroke, cognitive function [Mini-Mental State Examination (MMSE)], and depression [Patient Health Questionnaire-9 (PHQ-9)]; and we applied SPSS 24.0 for data analysis. Results: In this study, 305 patients with ischemic stroke were finally recruited, including 189 (61.97%) men, with an average age of 67 years. According to the mRS score, ischemic stroke patients were divided into patients without symptoms (controls, mRS = 0), patients without obvious disability (mRS = 1), and patients with mild to severe disability (mRS = 2–5). Ischemic stroke patients with different mRS levels demonstrated significant differences in age, tobacco smoke exposure, previous stroke history, cognitive function, and depression status. Compared with patients without symptoms (mRS = 0), patients with mRS = 1 had a lower MMSE score [odds ratio (OR): 0.48, 95% confidence interval (CI): 0.26–0.90]; and patients with mRS = 2–5 had a lower MMSE score [OR = 0.16, 95% CI: 0.08–0.33], had a higher PHQ-9 score [OR = 5.36, 95% CI: 2.19–13.11], and were more likely to have previous stroke history [OR = 2.18, 95% CI: 1.01–4.79]. Conclusion: Lower degrees of functional independence are related to cognitive impairment, as well as the previous stroke history and depression status.